Ukrainian companies in Poland - conditions and structure of foreign direct investment = Bezpośrednie inwestycje zagraniczne ukraińskich przedsiębiorstw w Polsce - uwarunkowania i struktura - Glinkowska, Beata (Zielona Góra: Faculty of Economics and Management Press)
The aim of the article is an attempt to find an answer to the question about the state of Ukrainian FDI in Poland: showing the state, support, government incentives, motives, barriers and investor sentiment. It was possible to reach the target primarily thanks to a thorough analysis of documentation from the websites of the State Statistics Service of Ukraine and interviews with representatives of institutions or their employees.
Keywords: internacjonalizacja; bezpośrednie inwestycje zagraniczne; BIZ; Ukraina; Polska; internationalization; foreign direct investment; FDI; Ukraine; Poland